Phyllodes Tumor in a Lactating Breast - Sudha S. Murthy; K. V. V. N. Raju; Haripreetha G. Nair (SAGE Publishing, 2016)
Phyllodes tumor is attributed to a small fraction of primary tumors of the breast. Such tumors occur rarely in pregnancy and lactation. We report a case of a 25-year-old lactating mother presenting with a lump in the left breast. Core needle biopsy was opined as phyllodes tumor with lactational changes, and subsequent wide local excision confirmed the diagnosis of benign phyllodes tumor with lactational changes. The characteristic gross and microscopic findings of a well-circumscribed lesion with leaf-like fibroepithelial growth pattern and typical nonuniform or diffuse stromal proliferation with periductal accentuation even in the absence of mitotic figures can help clinch the diagnosis. Benign phyllodes is known for its recurrence and requires wide excision and close follow-up. It is vital to identify these lesions even on limited biopsies as therapeutic options differ. This case is presented for its rarity and the diagnostic challenge it poses in limited biopsy.